Nonlinear dynamics : a primer - Medio, Alfredo, 1938- (Cambridge University Press, 2001)
A textbook on the theory of nonlinear dynamical systems for non-mathematical final-year undergraduate or graduate students, or a reference book for researchers, in the physical and social sciences. It provides a comprehensive introduction including linear systems, stability theory of nonlinear systems, bifurcation theory, chaotic dynamics.